The resilience of indigenous women of the U.S. who experience cancer: transcending adversity. Issue 3 (4th May 2021) - Burnette, Catherine E.; Roh, Soonhee; Liddell, Jessica; Lee, Yeon-Shim
ABSTRACT: Almost no research specifically explores resilience among Indigenous women of the U.S. who experience cancer. A qualitative descriptive study included a sample of 43 Indigenous women from the Northern Plains region of the U.S. Almost 90% (88%, n = 37) of participants indicated personal growth in response to having cancer, indicating they valued relationships (n = 3), had a stronger faith (n = 5), were grateful and living in moment (n = 21), became more healthy (n = 5), and helped others (n = 6) in response to their cancer experience. Results indicate that factors that promote and facilitate resilience are critical for culturally responsive practice with Indigenous women.